Breast cancer during pregnancy - Matos, Erika (Radiology and oncology (Ljubljana), 2021)
Pregnancy associated breast cancer is a rare disease. It presents a unique entity of breast cancer with aggressive phenotype. The main aim was to evaluate how the international guidelines were followed in daily practice. Patients and methods. Data concerning patients% and tumours% characteristics, management, delivery and ma-ternal outcome were recorded from institutional electronic database. In this paper a case series of pregnant breast cancer patients treated at single tertiary institution between 2007 and 2019 are presented and the key recommenda-tions on managing such patients are summarized.Results. Fourteen patients met the search criteria. The majority of tumours were high grade, triple negative or HER2 positive, two patients were de novo metastatic. Treatment plan was made for each patient by multidisciplinary team. Eight patients were treated with systemic chemotherapy with no excess toxicity or severe maternal/fetal adverse ef-fects. In all but two patients, delivery was on term and without major complications. Only one event, which was not in whole accordance with international guidelines, was identified. It was the use of blue dye in one patient.Conclusions. Women with pregnancy associated breast cancer should be managed like non-pregnant breast cancer patients and should expect a similar outcome, without causing harm to the unborn child. To achieve a good outcome in pregnancy associated breast cancer, a multidisciplinary approach is mandatory.
Keywords: breast cancer; clinical characteristics; klinične lastnosti; načini zdravljenja; nosečnost; pregnancy; rak dojke; therapeutic strategy